The Effects of Pond Type and Water Quality Dynamics on Vannamei Shrimp Growth: A Dummy Regression Analysis - Supriatin, Febriyani Eka; Rahmawati, Aulia; Dailami, Muhammad (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Vannamei shrimp is one of Indonesia's leading aquaculture sector commodities due to its high survival rate, short cultivation time, and disease resistance. Vannamei shrimp cultivation in Indonesia adopts an intensive system favoured for high productivity. In intensive cultivation systems, shrimp ponds typically utilize concrete or high-density polyethylene (HDPE) ponds. Each type has its own positive and negative side that affects the growth and production of Vannamei shrimp. Apart from the type of pond, water quality also played an important role in the growth of Vannamei shrimp. Water quality is one of the important factors in intensive shrimp cultivation. Pond type is categorical data and has a nominal measurement scale, while water quality is numerical data with a ratio measurement scale; ordinary regression analysis is unsuitable for analyzing the effect of pond type and water quality on the growth of Vannamei shrimp. Therefore, a dummy regression model accommodates these measurement scale differences. This research aims to determine the effect of different types of ponds and water quality dynamics on the growth of Vannamei shrimp and to select the best type of pond for intensive cultivation of Vannamei shrimp. Additionally, it aims to identify the water quality parameters that most influence the growth of Vannamei shrimp so that it can serve as a reference for Vannamei shrimp farmers to achieve high productivity efficiently. The study was conducted from November 2022 to January 2023 in Banyuwangi Regency, East Java Province, Indonesia. There are three concrete ponds and 10 HDPE ponds. The research method employed in this study is a survey method utilizing simple random sampling. The parameters in this research are the quality of cultivation water, including pH, temperature and dissolved oxygen (DO). The water samples taken are then measured for water quality in the laboratory. The results of this study indicate that the average values for water quality are still within the optimal range. The average ABW in HDPE and concrete ponds ranges from 2.30 to 9.39 grams per shrimp and 2.22-9.73 grams per shrimp. Based on the study's results, it can be concluded that different pond types and water quality dynamics, specifically pH and temperature, affect shrimp growth based on ABW. However, when considering SGR values, the type of pond does not have a significant impact. The water quality parameters that affect SGR are pH and temperature.